Risk stratification in normotensive acute pulmonary embolism patients: focus on the intermediate–high risk subgroup. Issue 4 (June 2020) - Santos, Ana Rita; Freitas, Pedro; Ferreira, Jorge; Oliveira, Afonso; Gonçalves, Mariana; Faria, Daniel; Bicho Augusto, João; Simões, Joana; Santos, Ana; Gago, Miguel; Oliveira, João; Antunes, Ricardo Mamede; et al.
Background: Patients with acute pulmonary embolism are at intermediate–high risk in the presence of imaging signs of right ventricular dysfunction plus one or more elevated cardiac biomarker. We hypothesised that intermediate–high risk patients with two elevated cardiac biomarkers and imaging signs of right ventricular dysfunction have a worse prognosis than those with one cardiac biomarker and imaging signs of right ventricular dysfunction. Methods: We analysed the cumulative presence of cardiac biomarkers and imaging signs of right ventricular dysfunction in 525 patients with intermediate risk pulmonary embolism (intermediate-high risk = 237) presenting at the emergency department in two centres. Studied endpoints were composites of all-cause mortality and/or rescue thrombolysis at 30 days (primary endpoint; n =58) and pulmonary embolism-related mortality and/or rescue thrombolysis at 30 days (secondary endpoint; n =40). Results: Patients who experienced the primary endpoint showed a higher proportion of elevated troponin (47% vs. 76%, P <0.001), elevated N-terminal pro-brain natriuretic peptide (67% vs. 93%, P <0.001) and imaging signs of right ventricular dysfunction (47% vs. 80%, P <0.001). Multivariate analysis revealed N-terminal pro-brain natriuretic peptide (hazard ratio (HR) 3.6, 95% confidence interval (CI) 1.3–10.3; P =0.015) and imaging signs of right ventricular dysfunction (HR 2.8, 95% CI 1.5–5.2; P =0.001) as independent predictors of events. In the intermediate–high risk group, patients with two cardiac biomarkers performed worse than those with one cardiac biomarker (HR 3.3, 95% CI 1.8–6.2; P =0.003). Conclusions: Risk stratification in normotensive pulmonary embolism should consider the cumulative presence of cardiac biomarkers and imaging signs of right ventricular dysfunction, especially in the intermediate–high risk subgroup.